(untitled) (Philology, 2026)
This study aims to mark the intersecting points visual media and literature deploy to construct the various modes through which transgressive fantasy, as conceived by William S. Burroughs and Andy Warhol, is articulated. Stemming from the artists’ experimentation with collage techniques, the research argues that the purpose of adopting such style not only creates cultural allusions but also generates an array of contradictory fantasies and desires, among which the desire for death is most explicitly stated. Despite the apparent discrepancies between Warhol’s poeticized representation of death in his Death and Disaster series, and Burroughs’s morbid infatuation with horrendous imagery in Naked Lunch, the aforementioned works constitute allegorical models of human suffering, developed via the implementation of various collage narrative mechanisms based on the "cut." Burroughs’s incorporation of radical cut-up technique adheres to “rhizomatic” narrative forms that operate on multiple levels, from stirring controversies and repugnance to proposing hypnotic obsession with death. Warhol’s manipulative use of collage images and repetition, in contrast, is intended to create visual oxymora, which, by revealing a commodified and beautified image of death, attempt to disrupt the audience’s perceptions.